(untitled) (Canadian Allergy & Immunology Today, 2024)
Over generations of health care providers, the approach to medicine has predominantly been reactive in nature, addressing symptoms as they arise. With advancements in medical research that explore the underlying mechanisms of disease, associated comorbidities, and improved therapeutic options, the objectives of medicine are transforming. While managing active symptoms remains crucial, there is a growing focus on altering the future trajectory of a disease which will result in new avenues to improve the quality of life of patients. In this evolving landscape, the atopic march emerges as a promising area for disease modification.